A 1-Tesla MRI system for dedicated brain imaging in the neonatal intensive care unit - Berson, Elisa R.; Mozayan, Ali; Peterec, Steven; Taylor, Sarah N.; Bamford, Nigel S.; Ment, Laura R.; Rowe, Erin; Lisse, Sean; Ehrlich, Lauren; Silva, Cicero T.; Goodman, T. Rob; Payabvash, Seyedmehdi (Frontiers in Neuroscience, 2023)
Objective: To assess the feasibility of a point-of-care 1-Tesla MRI for identification of intracranial pathologies within neonatal intensive care units (NICUs). Methods: Imaging and clinical findings of infants who had point-of-care 1-Tesla MRI in NICU (1/2021 to 1/2022) were evaluated and compared with other imaging modalities when available. Results: 60 infants had point-of-care 1-Tesla MRI; one scan was incompletely terminated due to motion. The average gestational age at scan time was 38.5±2.3 weeks. Transcranial ultrasound (n=46), 3-Tesla MRI (n=3), or both (n=4) were available for comparison in 53 (88%) infants. The most common indications for point-of-care 1-Tesla MRI were term corrected age scan for extremely preterm neonates (born at greater than 28 weeks gestation age, 42%), intraventricular hemorrhage (IVH) follow-up (33%), and suspected hypoxic injury (18%). The point-of-care 1-Tesla scan could identify ischemic lesions two infants with suspected hypoxic injury – both confirmed by follow-up 3-Tesla MRI. Utilizing 3-Tesla MRI, two lesions were identified which were not visualized on point-of-care 1-Tesla scan: (1) punctate parenchymal injury versus microhemorrhage; and (2) small layering IVH in an incomplete point-of-care 1-Tesla MRI with only DWI/ADC series, but detectable on the follow-up 3-Tesla ADC series. However, point-of-care 1-Tesla MRI could identify parenchymal microhemorrhages, which were not visualized on ultrasound. Conclusion: Although limited by field strength, pulse sequences, and patient weight (4.5 kg)/head circumference (38 cm) restrictions, the Embrace® point-of-care 1-Tesla MRI can identify clinically relevant intracranial pathologies in infants within a NICU setting.